Monica Alterskjær Olsen; Microbial digestion in reindeer and minke whales - Rolf Egil Haugerud (ed.) (Rangifer, 2000)
Monica Alterskjær Olsen defended her thesis; 'Microbial digestion in reindeer and minke whales' for the degree of Doctor Philosophiae at the University of Tromsø, Norway, April 2000. Olsen completed her Cand.Scient degree at Department of Arctic Biology, University of Tromsø in 1992. She conducted her doctoral work at the same department, where she is currently employed as an associate professor. Her doctoral thesis was based on seven papers.